PELAYANAN HAK – HAK PELANGGAN PT. GARUDA INDONESIA : STUDI KASUS PADA BENCANA KABUT ASAP DI PEKANBARU RIAU - Lia Sopiyah; Harapan Tua R.F.S (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Smoke haze happened in Riau in 2015 result in losses in sveral aspect, one of which in the field of transportation. Loss the most truth is air transport. Flight for smoke haze many tha were cancelled because of the smoke haze very thick so many a flight that in schedule it again. Airline Garuda Indonesia is air line so known as air line best in Southeast Asia so that PT. Garuda Indonesia have some strategy in serve the passengers for smoke haze so that right customers could be met. The purpose of this research is want to see how service the right customers PT. Garuda Indonesia in the case of disaster smoke haze in Pekanbaru Riau and know factorc anything influence it.Researches used the theory leach which states that service criteria that right customers that is the right to obtain good services, a right to know how decisions on the services certain made and the right to heard and be noticed opinionts. This research uses the method descriptive qualitative, techniuque data collectin through observation and interview where parties involved in this research as informants.The results ogf this study indicate that the right care customers right PT. Garuda Indonesia in case of Disaster Haze in Pekambaru in Riau have not done everything well where there are still some strategies from Pt. Garuda Indonesia is yet to be done. Factors – factors that affect performance rights – rights for customers in Pekanbaru Riau Haze is communication and coordination.Keyword : Public Services, Rights – the rights customers and PT. Garuda Indonesia